Factors influencing awareness of private sector servants towards the retirement planning / Atiqah Aminuddin @ Sahar and Raffael Rezza Ruzlan - Aminuddin @ Sahar, Atiqah; Ruzlan, Raffael Rezza (Faculty of Business and Management, 2014)
This paper is aimed to investigate the factors that influence the awareness of private sector servants towards the retirement planning. The factors that influenced the awareness of private sector servants towards retirement planning are future time perspective, financial knowledge and financial risk tolerance. The first objective of this study is to identify the relationship between the future time perspectives, financial knowledge and financial risk tolerance with awareness of private sector servants towards the retirement planning. Next, the purpose is to identify the most significant factors that influence the awareness of private sector servants towards the retirement planning. Primary data of this study is by distribute the questionnaire. In gathering the data, 200 set of questionnaire is distributed to private sector servants, but only 194 answered questionnaires are returned back. The reliability test, descriptive analysis, Pearson’s correlation and regression method are used for the data analysis. The Person’s correlation is used to find the significant relationship between those variables, while regression method is used to find the most significant variable. The findings show that only two variables managed to have significant result towards the dependent variable which is awareness of private sector servants towards the retirement planning and can be used in making prediction in this study. It is concluded that financial risk tolerance is the most significant factor that influence awareness of private sector servants towards the retirement planning. And it is recommended that future research on similar topic that focus on rural area or another urban area should be conducted.